Xin-Fu-Kang oral liquid improves cardiac function and attenuates miR-223–associated NF-κB/NLRP3 pyroptotic signaling in chronic heart failure - Ye, Zelin; Liu, Mingrui; Zhang, Xiaohan; Wu, Huaqin; Qiu, Zhiling; Chai, Ruoning; Hu, Yuanhui (Frontiers in Pharmacology, 2025)
BackgroundPyroptotic signaling involving nuclear factor-kappa B (NF-κB) and NOD-like receptor family pyrin domain–containing 3 (NLRP3) has been implicated in chronic heart failure (CHF). Xin-Fu-Kang (XFK) is a nine-herb formula used clinically for CHF with “qi deficiency and blood stasis.” Although cardioprotective effects have been reported, it remains unclear whether XFK modulates myocardial pyroptotic signaling via miR-223–dependent regulation of NF-κB.MethodsA CHF model was established by permanent left anterior descending coronary artery (LADCA) ligation in rats, and an in vitro oxygen–glucose deprivation/reoxygenation (OGD/R) injury model was generated in H9c2 cardiomyocytes. Cardiac structure and function were assessed by transthoracic echocardiography and histology. Myocardial inflammation and pyroptotic signaling were quantified by ELISA for interleukin-1 beta (IL-1β) and interleukin-18 (IL-18), and by immunoblotting for NLRP3, pro-caspase-1/caspase-1 ratio, Apoptosis-associated speck-like protein containing a CARD (ASC), cleaved gasdermin D N-terminal fragment (GSDMD-N), and NF-κB p65 phosphorylation. Nuclear–cytoplasmic fractionation and immunofluorescence tracked p65 translocation. Causality was probed by miR-223 gain- and loss-of-function, with functional rescue using a miR-223 inhibitor. RT-qPCR was used to measure the mRNA levels of NF-κB p65 and miR-223.ResultsLADCA produced marked systolic dysfunction with chamber dilation, increased myocardial IL-1β and IL-18, increased NLRP3, ASC, GSDMD-N, and p65 phosphorylation, and decreased the pro-caspase-1/caspase-1 ratio. XFK improved cardiac function and structural integrity, attenuated fibrosis and cardiomyocyte apoptosis, reduced inflammatory cytokines, and diminished NLRP3 and ASC abundance. In OGD/R-injured H9c2 cells, XFK preserved viability, limited lactate dehydrogenase release, decreased NLRP3, ASC, GSDMD-N, and IL-1β, increased the pro-caspase-1/caspase-1 ratio, and restrained NF-κB activation by reducing p65 phosphorylation and nuclear translocation. Mechanistically, XFK upregulated miR-223, and miR-223 overexpression reproduced the suppression of pyroptosis-related readouts linked to NF-κB/NLRP3 signaling. Inhibition of miR-223 attenuated the protective effects of XFK, supporting the interpretation that XFK-mediated modulation of NF-κB-related inflammatory signaling is at least partly dependent on miR-223.ConclusionNF-κB–linked NLRP3 pyroptotic signaling represents a prominent feature in the CHF model examined. These findings suggest that XFK exerts protective effects in CHF via miR-223–dependent modulation of NF-κB/NLRP3 pyroptotic signaling, supporting its potential adjunctive strategy to mitigate inflammation-driven cardiac dysfunction.